(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the clinical and epidemiological features of enteral (A, E) hepatitis at the present stage, to master the criteria for early clinical and laboratory diagnosis of acute viral hepatitis, the principles of differential diagnosis in different periods of the disease, treatment methods depending on the severity of acute hepatitis, management tactics and dispensary observation of patients after discharge from the hospital, anti-epidemic measures in the outbreak, principles of specific prevention and their implementation in practice.